2018
DOI: 10.3390/cryptography2040039
|View full text |Cite
|
Sign up to set email alerts
|

Security and Cryptographic Challenges for Authentication Based on Biometrics Data

Abstract: Authentication systems based on biometrics characteristics and data represents one of the most important trend in the evolution of the society, e.g., Smart City, Internet-of-Things (IoT), Cloud Computing, Big Data. In the near future, biometrics systems will be everywhere in the society, such as government, education, smart cities, banks etc. Due to its uniqueness, characteristic, biometrics systems will become more and more vulnerable, privacy being one of the most important challenges. The classic cryptograp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…In this phase the CSK modulation idea is employed to encode generated shares S A and S B which are treated as signals to generate two noise signals = Share1 and Share2 based on CSK modulation as presented, in algorithm (2). The sent signal can be expressed as follows ( ), 1 () ( ), 0…”
Section: B Coding Phasementioning
confidence: 99%
See 1 more Smart Citation
“…In this phase the CSK modulation idea is employed to encode generated shares S A and S B which are treated as signals to generate two noise signals = Share1 and Share2 based on CSK modulation as presented, in algorithm (2). The sent signal can be expressed as follows ( ), 1 () ( ), 0…”
Section: B Coding Phasementioning
confidence: 99%
“…Because of their uniqueness, characteristic biometrics systems will become more vulnerable, and privacy will be one of the most important challenges. Classic cryptographic primitives are not appropriate to ensure a strong level of privacy security [2].…”
Section: Introductionmentioning
confidence: 99%
“…For analysis, the sample areas of 400 × 400 mm 2 with a distance of 10 µm between adjacent profiles, at a scanning rate of 100 µm/s, and an applied mass of 0.5 mg, were used. The results were analyzed via APEX 3D BASIC V7USA, (Milpitas, CA, USA) dedicated software and the density of square unit per surface area was calculated using the Abbott-Firestone algorithm, a cumulative probability density function of the total measured heights [32][33][34].…”
Section: Substrates Topography Characterizationmentioning
confidence: 99%
“…Elkamchouchi et al [23] suggested method of cryptography which uses the image as an open key and arbitrary integers as a private key to compute the image [24]. Jain et al [25], suggested a steganography to hide biometric data (fingerprint minutiae) in multitude images (face), whose function is to transmit the data.…”
Section: A Vulnerabilities Attacks Of Biometric Template In the Datamentioning
confidence: 99%